(untitled) (Colombia Medica, 1992)
Continuous recordings of intramammary pressure performed in 158 normal lactating women between the first and the 6th postpartum day were retrospectively analyzed to define the pattern of neurohypophyseal release of endogenous oxytocin both during the baby’s suckling and during the appearance of spurts of spontaneous milk ejecting activity. Mammary responses were duplicated by administering IV injections of Knox doses of oxytocin. Baby’s suckling induced a pulsatile release pattern. On the contrary, spontaneous milk ejecting activity showed a simple release pattern of the hormone. The physiological significance of these findings is discussed.